Molecular Pathology of Lung Diseases - Zander, Dani S.; Zander, Dani S.; Popper, Helmut.; Popper, Helmut.; Jagirdar, Jaishree.; Jagirdar, Jaishree.; Haque, Abida.; Haque, Abida.; Barrios, Roberto.; Barrios, Roberto. (Molecular Pathology Library, 2008)
Molecular Pathology of Lung Diseases, the first volume in the Molecular Pathology Library Series under the series editorship of Philip T. Cagle, MD provides a bridge between clinical pulmonary pathology and basic molecular science. It is designed to provide a practical disease-based overview that will be useful to pathologists, pulmonologists, thoracic surgeons and other health care providers interested in lung disease. The first two sections of the volume provide the reader with general concepts, terminology and procedures in molecular pathology. The remainder of the volume is subdivided into neoplastic and non-neoplastic lung diseases with detailed chapters covering the current molecular pathology of specific diseases.